Attenuation of Angiotensin II–Induced Hypertension in BubR1 Low‐Expression Mice Via Repression of Angiotensin II Receptor 1 Overexpression. Issue 23 (3rd December 2019) - Aoyagi, Yukihiko; Furuyama, Tadashi; Inoue, Kentaro; Matsuda, Daisuke; Matsubara, Yutaka; Okahara, Arihide; Ago, Tetsuro; Nakashima, Yutaka; Mori, Masaki; Matsumoto, Takuya
Abstract : Background: Angiotensin II (Ang II) can cause hypertension and tissue impairment via AGTR1 (Ang II receptor type 1), particularly in renal proximal tubule cells, and can cause DNA damage in renal cells via nicotinamide adenine dinucleotide phosphate oxidase. BubR1 (budding uninhibited by benzimidazole‐related 1) is a multifaceted kinase that functions as a mitotic checkpoint. BubR1 expression can be induced by Ang II in smooth muscle cells in vitro, but the relationship between systemic BubR1 expression and the Ang II response is unclear. Methods and Results: Twenty 24‐week‐old male BubR1 low‐expression mice (BubR1 L/L mice) and age‐matched BubR1 +/+ mice were used in this study. We investigated how Ang II stimulation affects BubR1 L/L mice. The elevated systolic blood pressure caused by Ang II stimulation in BubR1 +/+ mice was significantly attenuated in BubR1 L/L mice. Additionally, an attenuated level of Ang II–induced perivascular fibrosis was observed in the kidneys of BubR1 L/L mice. Immunohistochemistry revealed that the overexpression of AGTR1 induced by Ang II stimulation was repressed in BubR1 L/L mice. We evaluated AGTR1 and Nox‐4 (nicotinamide adenine dinucleotide phosphate oxidase‐4) levels to determine the role of BubR1 in the Ang II response. Results from in vitro assays of renal proximal tubule cells suggest that treatment with small interfering RNA targeting BubR1 suppressed Ang II‐induced overexpression of AGTR1. Similarly, the upregulation in Nox4 and Jun N‐terminal kinase induced by Ang II administration was repressed by treatment with small interfering RNA targeting BubR1. Conclusions: Ang II–induced hypertension is caused by AGTR1 overexpression in the kidneys via the upregulation of BubR1 and Nox4.